2001
DOI: 10.3727/000000001783986260
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Foam/Spheroid Culture System Using Human Hepatoblastoma Cell Line (Hep G2) as a Possible New Hybrid Artificial Liver

Abstract: The risk of xenozoonosis infections poses the greatest obstacle against the clinical application of hybrid artificial liver support system (HALSS). Primary human hepatocytes are an ideal source for HALSS, but the shortage of human livers available for hepatocyte isolation limits this modality. To resolve this issue, we used human hepatocytes with replication capacity (fetal hepatocytes, Hep G2, and Huh 7) in a polyurethane foam (PUF)/spheroid culture system in vitro, and analyzed liver functions such as ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…These spheroids have a structure similar to actual liver tissues and can maintain a higher level of liver-specific functions over a longer period of time (Landry et al, 1985;Koide et al, 1990;Tong et al, 1992;Peshwa et al, 1996;Selden et al, 2000;Khalil et al, 2001;Abu-Absi et al, 2002;Depreter et al, 2002). Therefore, various applications have been proposed for these spheroid cultures, including bioartificial livers and liver tissue engineering as well as an in vitro model for studying drug metabolism and hepatotoxicity (Harries et al, 2001;Yamashita et al, 2001;Fukuda et al, 2003;Xu et al, 2003;Otsuka et al, 2004;Fukuda and Nakazawa 2005;Fukuda et al, 2006). However, it is difficult to control the diameter of spheroids grown in these cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These spheroids have a structure similar to actual liver tissues and can maintain a higher level of liver-specific functions over a longer period of time (Landry et al, 1985;Koide et al, 1990;Tong et al, 1992;Peshwa et al, 1996;Selden et al, 2000;Khalil et al, 2001;Abu-Absi et al, 2002;Depreter et al, 2002). Therefore, various applications have been proposed for these spheroid cultures, including bioartificial livers and liver tissue engineering as well as an in vitro model for studying drug metabolism and hepatotoxicity (Harries et al, 2001;Yamashita et al, 2001;Fukuda et al, 2003;Xu et al, 2003;Otsuka et al, 2004;Fukuda and Nakazawa 2005;Fukuda et al, 2006). However, it is difficult to control the diameter of spheroids grown in these cultures.…”
Section: Discussionmentioning
confidence: 99%
“…One such system involves culturing cells on scaffold surfaces in conjunction with the use of proteoglycan, causing the cells to undergo cellcell interaction rather than cell-substratum interaction (Koide et al, 1990). Similar systems involve the use of poly-(2-hydroxyethylmethacrylate) (Landry et al, 1985;Tong et al, 1992) (Tobe et al, 1992), galactosylated materials (Lin et al, 1995) or poly-N-isopropyl acrylamide (Takezawa et al, 1992), and 3D scaffolds (Yamashita et al, 2001;Fukuda et al, 2003). Other systems designed to create spheroid cultures include the hanging drop method, the rotating culture system, the agitating culture system, microfabricated chips, and the microspace cell culture system (Sakai et al, 1996;Yamada et al, 1998;Kelm et al, 2003;Sakai and Nakazawa, 2007;Nakamura et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that a human hepatoblastoma cell line (Hep G2) has high liver-specific ment. functions among human cell lines (Huh-7 and fetal hePreparation of PH patocytes) in the PUF stationary culture (31).…”
Section: Introductionmentioning
confidence: 99%
“…Spheroid culture is effective in the upregulation of liver-specific functions of primary adult hepatocytes and human hepatoma cell lines (Matsushita et al 1991;Yamashita et al 2001), and in the reorganization of new-born rat hepatocytes (Landry et al 1985). This study investigated the proliferation of normal human fetal hepatocytes in vitro and the restoration of their functions by forming spheroids cultured on a suitable surface of a culture dish modified with poly-L-amino acids.…”
Section: Introductionmentioning
confidence: 99%